Economic Space Movement: Shifting Functions of Semarang Suburban Land at the Beginning of the 21st Century - Utami, Santi Muji; Setiawati, Nur Aini; Marta, Nur Aeni (Indonesian Historical Studies, 2024)
In long-term planning, the central area of Semarang City is intended to serve as a centre for government, business development, and trade. As a result, more and more settlements are being evicted or marginalized. The manufacturing industry was relocated for business expansion, so it needed new land both to develop activities and provide supporting facilities. These two sectors eventually shifted to the city's outskirts, causing spatial transformation in suburban areas. This research was conducted as social research with an environmental history approach. The problem that arises is how suburban areas should move due to changes in land use and significant increases in land values. This study applies qualitative research methods with a historical approach to look at phenomena that occur in the suburbs of Semarang. The research results show that, in the 21st century, rice fields and swamps in the eastern region of Semarang City have been converted into industrial areas. This area connects Semarang City with cities in the eastern region of Java Island. Meanwhile, the western part of the city of Semarang, with its flat topography and close to the coast, has become an industrial area and is also being built for residential purposes. Both are close to Tanjung Emas Harbor. Increasingly intensive changes in land use have caused land prices to increase significantly yearly.